Penerapan Instrumen Remedial-Pengayaan melalui Teks Naratif "Ketulusan" Upaya Peningkatan Menyimak dan Komunikasi Kelas VI - Soviana, Soviana; Purwati, Panca Dewi (YASIN, 2025)
Listening and oral communication are fundamental competencies for elementary school students; however, in classroom practice many pupils still struggle to understand texts in depth, partly due to the limited variety of instructional strategies that can accommodate differences in students’ abilities. This study aims to analyze the effectiveness of implementing remedial and enrichment instruments using the narrative text “Ketulusan” as an effort to improve listening and oral communication skills among sixth-grade students at SD Wonoplembon 02. The research employed a mixed-methods approach with an Explanatory Sequential design, beginning with in-depth qualitative exploration followed by quantitative data collection. The findings show a significant improvement in listening skills, with an average enrichment score of 88.14, as well as an increase in oral communication skills, with an average score of 85.76. These results indicate that the use of narrative texts and a differentiated learning approach through a remedial–enrichment scheme effectively helps students understand story content and retell information in a coherent and clear manner. Accordingly, the instrument is proven effective in enhancing the two language competence aspects that constitute the focus of this study and reinforces the importance of implementing instructional strategies that are adaptive to students’ diverse abilities in Bahasa Indonesia learning at the elementary school level.